Genetic algorithm‐based multiple moving target reaching using a fleet of sailboats. Issue 3 (12th December 2019) - Christophe, Viel; Ulysse, Vaultier; Jian, Wan; Luc, Jaulin
Abstract : This study addresses the problem of Dynamic Travelling Salesman Problem for a multi‐agent system using a fleet of sailboats. A genetic algorithm (GA) is proposed, which attributes to each agent a varying number of targets to be collected. GA allows obtaining a suboptimal solution in the shortest time possible. Moreover, this study adapts it to the specific problem involving a fleet of sailboats, which is a challenging task with comparison to autonomous underwater vehicles or motorised vehicles in terms of the propulsion. Therein motors can be flexibly controlled while sailboat movements are constrained by available wind direction and speed. Thus the method takes into account wind conditions at various locations of the sailboat. Simulation results demonstrate the effectiveness of the proposed approach.